Konsep SQ: Kecerdasan Spiritual Menurut Danah Zohar Dan Ian Marshal Dan Relevansinya Terhadap Tujuan Pembelajaran PAI - Sri Haryanto; Soffan Rizki; Mahdi Fahdilah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
In the treasury of Indonesian educational literacy the book "(SQ) Spiritual Intelligence", is a written work in the popular-psychology category as a result of the thoughts and contemplation of a psychologist Danah Zohar and Ian Marshal which will later be presented on the values of transcendent Islamic educational methods to students. We need to know that the real method of Islamic Education is to print generation after generation so that they always lead to good and intelligent human beings, then also all the potential of their intelligence as human nature can grow optimally. However, the tragedy in our current education is that Islamic education is only a method to elevate intellectual intelligence (IQ), in the same way it only deals with the mere transfer of knowledge at the practical level. With regards to Islamic education methods, this is about encouraging religiously intelligent students. However, in the sense that students do not experience a moral decline, children who use this method have a monotheistic (integral) mindset and are able to associate attitudes and actions in everyday life.